Pengaruh Pemberian "Probioticum" dalam Ransum Ayam Pedaging terhadap beberapa Organ Tubuh - Lidy Herawaty; Anggorodi Anggorodi; Lily Amalia Sofyan (Buletin Ilmu Makanan Ternak, 1987)
A study was carried out to investigate the effects of different levels of PROBIOTICUM on the performance of two hundred Tatum Broiler female day-old chicks. Treatment were the basal comsoy based diet with the following supplemental PROBIOTICUM levels : 0, 50, 75, 100 and 125 ppm. Feed and water were supplied ad libitum in all trials.The design was a 4 replicate of 5 treatments. The trial started at December 21, 1984 and terminated February 15, 1985.The chicks produced showed no significant differences in body weight and in any of the organ weights examined. The results also show o highly significant (P/0.01) increase in the weight of the gastro-intestinal fat from the birds fed the higher level of PROBIOTICUM when compared to those fed the basal diet.       From all the results it apperars that under the conditions of this study, a ration containing; 100 ppm PROBIOTICUM will be adequate for optimum broiler production.